Metabolic toxicities in patients undergoing treatment for nonhematological malignancy: A cross-sectional study - Subhash Gupta; Kunhi Parambath Haresh; Soumyajit Roy; Lakhan Kashyap; Narayan Adhikari; Rambha Pandey; Dayanand Sharma; Pramod Kumar Julka; Goura Kishor Rath (Indian Journal of Medical and Paediatric Oncology)
Objectives: The objective of this study was to evaluate the prevalence of metabolic toxicities in patients with different nonhematological malignancies admitted in oncology ward of a tertiary cancer care center while on treatment. Methods: We did this cross-sectional study over a period of 7 months (January–July 2013) for all adult patients (n = 280) who, while undergoing anti-cancer therapy at our center, got admitted to our oncology inpatient ward with metabolic toxicity. Grading of toxicity was done using National Cancer Institute Common Terminology Criteria for Adverse Events Version 4.0. Results: A total of 46 events of metabolic toxicities were noted in 31 patients over this period. The most common of them was hyperglycemia (n = 10). The others were hypokalemia (n = 9), hyponatremia (n = 9), hypernatremia (n = 5), hyperkalemia (n = 5), tumor lysis syndrome (n = 4), hypercalcemia (n = 2), and grade ≤2 hypomagnesemia (n = 2). Majority of the patients were asymptomatic (n = 26). However, death occurred in five patients. Treatment interruptions took place in 19 patients. Age ≤40 years (P = 0.03), Eastern Cooperative Oncology Group performance status ≥2 (P = 0.023), history of addiction (P = 0.02), comorbidities (P = 0.037) were associated with increased risk of having metabolic toxicities on univariate analysis. While on multivariate analysis, only age, performance status, and history of addiction retained their statistical significance. Age ≤40 years (P = 0.02), use of more than one modality of treatment (P = 0.021), and hyperglycemia (P = 0.042) were associated with higher risk of death. Conclusion: Metabolic toxicities are common phenomena among cancer patients, especially those with young age, comorbidities, and having history of addictions. In young age, they might even be fatal, especially when they are treated with combined modality of treatment.